Danish as a Window Onto Language Processing and Learning. Issue 3 (12th March 2021) - Trecca, Fabio; Tylén, Kristian; Højen, Anders; Christiansen, Morten H.
Abstract: It is often assumed that all languages are fundamentally the same. This assumption has been challenged by research in linguistic typology and language evolution, but questions of language learning and use have largely been left aside. Here we review recent work on Danish that provides new insights into these questions. Unlike closely related languages, Danish has an unusually reduced phonetic structure, which seemingly delays Danish‐learning children in several aspects of their language acquisition. Adult language use appears to be affected as well, resulting, among other things, in an increased dependence on top‐down information in comprehension. In this conceptual review, we build the argument that a causal relationship may exist between the sound structure of Danish and the peculiarities of its acquisition and use. We argue that a theory of language learning that accommodates the existing evidence from Danish must explicitly account for the interaction between learner‐related factors and language‐specific constraints. Abstract :